miR-132/212 Impairs Cardiomyocytes Contractility in the Failing Heart by Suppressing SERCA2a - Lei, Zhiyong; Wahlquist, Christine; el Azzouzi, Hamid; Deddens, Janine C.; Kuster, Diederik; van Mil, Alain; Rojas-Munoz, Agustin; Huibers, Manon M.; Mercola, Mark; de Weger, Roel; Van der Velden, Jolanda; Xiao, Junjie; et al. (Frontiers in Cardiovascular Medicine, 2021)
Compromised cardiac function is a hallmark for heart failure, mostly appearing as decreased contractile capacity due to dysregulated calcium handling. Unfortunately, the underlying mechanism causing impaired calcium handling is still not fully understood. Previously the miR-132/212 family was identified as a regulator of cardiac function in the failing mouse heart, and pharmaceutically inhibition of miR-132 is beneficial for heart failure. In this study, we further investigated the molecular mechanisms of miR-132/212 in modulating cardiomyocyte contractility in the context of the pathological progression of heart failure. We found that upregulated miR-132/212 expressions in all examined hypertrophic heart failure mice models. The overexpression of miR-132/212 prolongs calcium decay in isolated neonatal rat cardiomyocytes, whereas cardiomyocytes isolated from miR-132/212 KO mice display enhanced contractility in comparison to wild type controls. In response to chronic pressure-overload, miR-132/212 KO mice exhibited a blunted deterioration of cardiac function. Using a combination of biochemical approaches and in vitro assays, we confirmed that miR-132/212 regulates SERCA2a by targeting the 3′-end untranslated region of SERCA2a. Additionally, we also confirmed PTEN as a direct target of miR-132/212 and potentially participates in the cardiac response to miR132/212. In end-stage heart failure patients, miR-132/212 is upregulated and correlates with reduced SERCA2a expression. The up-regulation of miR-132/212 in heart failure impairs cardiac contractile function by targeting SERCA2a, suggesting that pharmaceutical inhibition of miR-132/212 might be a promising therapeutic approach to promote cardiac function in heart failure patients.